State Cutbacks to Medicaid May Hit Hospitals Hard: New Federal Reductions Might Compound the Stress - Barlas, Stephen (MediMedia USA, Inc., 2012)
Hospitals, low-income families, and disabled individuals who rely on Medicaid funding will be struggling financially if the government reduces its outlays to the states by $800 billion over the next 10 years in order to reduce the federal deficit.